Tillage Effects on Soil Biochemical Properties and Maize Grown in Latosolic Red Soil of Southern China - Evans Asenso; Jiuhao Li; Lian Hu; Fuseini Issaka; Kai Tian; Lina Zhang; Luyong Zhang; Haibo Chen (Applied and Environmental Soil Science)
Based on the hypothesis that soil biochemical and maize yield components should be affected by different tillage methods, a field experiment was conducted to study the effects of subsoiling (SS), two passes of rotary tillage (2RT), two passes of rotary tillage + subsoiling (2RTSS), and zero tillage (ZT) on distribution of organic C, available NPK and soil enzyme, and its effects on maize yield in latosolic red soil of southern China in 2016 and 2017. ZT treatment had significantly higher organic C and available NPK than the other treatments, whereas the SS treatment had higher concentration of soil urease, catalase, and acid phosphatase. Also, maximum grain yield, dry matter, harvest index, and 1000-grain weight were recorded under SS treatment. Overall, although ZT facilitated more organic C and available NPK, soil with ZT had lower soil enzyme and maize yield components compared to SS treatment, and therefore SS treatment could be exploited as a strategy for soil health and productivity resulting in a sustainable agricultural system.